Ecotherapy in the Tibb Nabawi perspective: An initial approach to holistic mental health - Dzulfaidhi Hakimie Dzulraidi; Mohd Solleh Ab Razak; Umar Muhammad Noor; Mohd Dahlan A. Malek (IDEAS, 2025)
Ecotherapy is increasingly accepted in modern medicine, emphasizing the therapeutic role of nature in supporting mental well-being. While ecotherapy is widely acknowledged in contemporary health practices, no comprehensive studies have explored this concept within the framework of Prophetic Medicine (Tibb Nabawi). Tibb Nabawi incorporates natural elements, such as water, herbs, and open spaces, commonly used for physical healing. However, the potential psychological and spiritual benefits of these elements, especially in enhancing mental well-being, have not been thoroughly examined. This study aims to address this gap by analyzing the foundational principles of Tibb Nabawi that align with ecotherapy and exploring how these elements can contribute to a holistic mental health approach. A qualitative methodology was employed, using textual analysis of relevant hadiths and classical Islamic texts to identify natural elements within Tibb Nabawi that support mental well-being. Content analysis was then applied to assess how these natural components can provide benefits that promote mental balance and spiritual wellness. The study finds that principles in Tibb Nabawi, such as contemplation (tadabbur) and reflection (tafakkur) on nature, are consistent with modern ecotherapy practices. This is evidenced by the Prophet Muhammad's (SAW) practices of secluding in the Cave of Hira and gazing at the night sky. These findings highlight the holistic nature of Prophetic teachings, which advocate a balanced lifestyle in harmony with the natural environment. The implications of this study suggest that Nabawi ecotherapy could offer a nature-based and faith-aligned alternative for supporting mental health, particularly among Muslim communities seeking culturally relevant care models. Further research could explore specific elements of nature therapy, such as water therapy (through ablution or viewing rivers) and green therapy (appreciating the beauty of forests and gardens), to enrich the concept of Nabawi Ecotherapy in the context of Islamic-based mental health.